Looking East : Carolus Linnaeus and His Herpetological Species from Asia - Das, Indraneil (International Society for the History and Bibliography of Herpetology, ISHBH, 2012)
Linnaean names based on material from Asia, indicated as from “Oriente”, “Indiis” or extralimital areas, are reviewed. This material, representing 31 species names and 29 recognizable biological species, can be restricted geographically to one of three regions—Sri Lanka, southern Malay Peninsula, or Java— although it is conceivable that some of these could have been collected from adjacent regions where these species co-occur. A number of specimens purported to be from the region have been shown by subsequent authors to be extralimital. The presumed points of origin are along trade routes in the East, where seventeenth century maritime trade (spices, timber, textiles) took place, and the vast majority of species are abundant, lowland species of such areas. Keywords: Linnaeus, “Oriente”,